Product Involvement Level, High-Priced Apparel and Consumers’ Post- Purchase Dissonance in Kathmandu Metropolitan City - Dhruba Lal Pandey,; Nischal Risal,; Bhupindra Jung Basnet,; Ayusha Adhikari, (Pravaha, 2023)
The study aims in analyzing the product involvement and post-purchase dissonance among consumers of high-priced apparel in Kathmandu Metropolitan City. Utilizing the Theory of Cognitive Dissonance and Self-Congruity Theory, the study examines how these psychological concepts influence consumer regret and satisfaction. In this context, product involvement is considered the independent variable, post-purchase dissonance the dependent variable, and income status, categorized into high and low, as the moderating variable. The study aims to identify factors driving consumer effort and remorse, analyze differences in product involvement and dissonance across income groups, and explore the relationship between product involvement and dissonance. Surprisingly, this study demonstrates that the influence of product involvement on post- purchase dissonance is minimal, with both high-income and low-income consumers exhibiting comparable levels of regret and dissatisfaction with their apparel purchases. The findings highlight a consistent pattern across different income groups, with no substantial differences in their return behaviors or product evaluations. Additionally, the weak correlation between product involvement and post-purchase dissonance suggests that increased involvement in the purchase decision does not significantly alter the level of consumer regret. Gender and age-related patterns show that both males and females experience post-purchase dissonance, and younger consumers are more engaged with product reviews and ratings. These insights offer valuable implications for understanding consumer behavior in the high-priced apparel market and can guide companies in refining their marketing strategies to better meet consumer expectations and mitigate dissatisfaction.